THE PROBLEM OF EQUIVALENCE IN THE TRANSLATION OF REALIA: A THEORETICAL ANALYSIS - Elena E. Deberdeeva ,Khasanova Dildora Shukhratovna (International Journal of Literature and Language Studies, 2026)
The translation of realia—culture-specific words and expressions denoting objects, phenomena, or concepts characteristic of a particular nation—presents one of the most persistent challenges in translation studies. This article examines the theoretical foundations of equivalence as applied to linguocultural realia, analyzing the tension between semantic fidelity and cultural accessibility. Drawing on equivalence theory, the study explores how translators navigate situations where direct lexical correspondences are absent between source and target languages. The analysis demonstrates that equivalence in realia translation operates on multiple levels—lexical, semantic, pragmatic, and cultural—and that the translator's choice of strategy depends on text type, audience expectations, and the sociocultural distance between the communicating communities. The article concludes that absolute equivalence is theoretically unattainable in realia translation; instead, translators must pursue functional equivalence that preserves the cultural information load while ensuring comprehensibility for the target audience.